Galería, drawings by Elio Naccarella (Mayéutica Revista Científica de Humanidades y Artes, 2019)
In Galería we present the collection of drawings made by the Venezuelan Italo sculptor and painter Elio Naccarella, with a long career in our country. His creative journey had as an end stage an intense artistic work in the state of Lara, where he died in 2014. Naccarella elaborated these drawings with which he illustrated the series of stories written by children who participated in the II Concurso Literario Infantil, organized by the Ateneo de Cabudare in 2002.